2016
DOI: 10.5888/pcd13.160247
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Perceptions of Physical Activity Facilitators and Barriers Among Women in Rural Southernmost Illinois

Abstract: IntroductionWomen living in rural areas in the United States experience disproportionately high rates of diseases such as obesity and heart disease and are less likely than women living in urban areas to meet daily physical activity (PA) recommendations. The purpose of our research was to understand age-specific perceptions of barriers and facilitators to rural women engaging in PA and to identify strategies to promote PA among these women.MethodsAs part of a community health assessment to learn about women’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The same occurred with the social factors, that affected the behavior of the diagnosed women more than the women without diagnosis. The most mentioned barriers to PA related to the social factors in previous studies are the lack of money, lack of knowledge, lack of time and the absence of free programs aiming to promote PA, corroborating the results of our study 10,[12][13][14]16,17,19,[23][24][25][26][27]29,30,32,33 . These findings regarding women's perceived barriers recognize that multiple reasons can inhibit regular PA engagement, and some of these factors are related to the socioeconomic status of these women.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The same occurred with the social factors, that affected the behavior of the diagnosed women more than the women without diagnosis. The most mentioned barriers to PA related to the social factors in previous studies are the lack of money, lack of knowledge, lack of time and the absence of free programs aiming to promote PA, corroborating the results of our study 10,[12][13][14]16,17,19,[23][24][25][26][27]29,30,32,33 . These findings regarding women's perceived barriers recognize that multiple reasons can inhibit regular PA engagement, and some of these factors are related to the socioeconomic status of these women.…”
Section: Resultssupporting
confidence: 91%
“…In addition, these findings add to the grow- Our study observed that the environmental factors influenced more the behavior of the women affected by breast cancer in comparison to the women without the diagnosis. Most of the environmental factors mentioned in previous studies are the difficulty in accessing the public transport, the lack of an adequate facility in the neighborhood, climate, traffic, overwork and lack of safety, in which the current study also reported similar barriers to practice PA 5,[6][7][8][9][11][12][13][14]16,19,20,25,26,28,31,32 . The same occurred with the social factors, that affected the behavior of the diagnosed women more than the women without diagnosis.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Objective aspects of the environment as well as individuals’ perceptions of their environment are likely to be important influences [ 17 ]. As rural communities are highly heterogeneous, factors influencing rural physical activity vary substantially across rural built environment studies, depending on the geographic and social contexts of the population being studied [ 8 , 18 , 19 , 20 , 21 ]. Given this, it is advantageous to use a variety of data sources to understand the various dimensions and support a more nuanced interpretation of barriers and facilitators.…”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively promote Rural men, masculinity and physical activity PA among rural men, mechanisms to encourage PA should consider the intersections of masculinity and rurality, given that men's perceptions of masculinity are related to their health behaviors [7,38]. This may be particularly relevant in rural populations that have unique challenges to being physically active, including a scarcity of PA resources, dispersed populations and land use, and great geographic distances to town centers [39,40]. Additional qualitative and quantitative research can further our knowledge of sex differences related to PA engagement and outcomes in rural populations.…”
Section: Discussionmentioning
confidence: 99%